A Metal-Ligand Cooperative Pathway for Intermolecular Oxa-Michael Additions to Unsaturated Nitriles - Perdriau, Sébastien; Zijlstra, Douwe S.; Heeres, Hero J.; de Vries, Johannes G.; Otten, Edwin (Angewandte Chemie International Edition, 2015)
An unprecedented catalytic pathway for oxa‐Michael addition reactions of alcohols to unsaturated nitriles has been revealed using a PNN pincer ruthenium catalyst with a dearomatized pyridine backbone. The isolation of a catalytically competent Ru–dieneamido complex from the reaction between the Ru catalyst and pentenenitrile in combination with DFT calculations supports a mechanism in which activation of the nitrile through metal–ligand cooperativity is a key step. The nitrile‐derived Ru‐N moiety is sufficiently Brønsted basic to activate the alcohol and initiate conjugate addition of the alkoxide to the α,β‐unsaturated fragment. This reaction proceeds in a concerted manner and involves a six‐membered transition state. These features allow the reaction to proceed at ambient temperature in the absence of external base. It all adds up: A novel pathway for oxa‐Michael addition to challenging β‐substituted unsaturated nitrile substrates is described based on a dearomatized ruthenium PNN pincer catalyst (see picture). Metal–ligand cooperative activation of the nitrile is key to the observed reactivity.